Levels of amino acids and related compounds in bronchoalveolar lavage fluids of asthmatic patients - Hofford, J M; Milakofsky, L; Pell, S; Fish, J E; Peters, S P; Pollice, M; Vogel, W H (American journal of respiratory and critical care medicine, 1997)
The constituents of bronchoalveolar lavage (BAL) fluid have been shown to reflect the presence and possible etiology of several pulmonary diseases. Presently, although research studies have reported the concentrations of cytokines and compounds such as major basic protein in BAL fluids, only the cellular elements, total protein, albumin, and immunoglobulins have been well defined. We hypothesize that amino acids and related amino compounds, well known participants in physiologic and biochemical processes, are present in BAL fluid and may have involvement in asthma. Our objective was to extend knowledge of the total chemical profile and clinical value of BAL fluids in humans by measuring these amino compounds in normal control subjects and asthmatic patients. Analysis by high-pressure liquid chromatography revealed the presence of 25 compounds. A few compounds in control subjects and patients were found to have values > 1.0 nmol/ml, while the majority were present in comparatively low concentrations < 1.0 nmol/ml. Asparagine, phosphoethanolamine, and taurine were significantly increased in the asthmatic patients. We conclude that the present profile of amino acids and related amino compounds in BAL fluid serves as a potential diagnostic tool in the study of various pulmonary disorders. The significance of increased asparagine, phosphoethanolamine, and taurine in the asthmatic patients is discussed and deserves further study.